Anciens et nouveaux parias. Des usages des migrations et du transit dans la politique libyenne - Saïd Haddad (Revue des Mondes Musulmans et de la Méditerranée)
Reinvesting in Africa during the years of embargo was the first step in al Qaddafi’s Libyan strategy to break its international isolation (1992-1999). After the suspension of the embargo, Libya’s foreign policy aimed at restoring economic and political ties with the West.But post-embargo Libya is also facing the rise of a large African migration, the result of Libyan diplomacy to reinvest in Africa. Traditionally considered a receiving country, Libya is now becoming a land of emigration.The study of migration to (and from) Libya offers an illustration of the way a southern Mediterranean country - and a former rogue state – puts it to use in the field of diplomacy, especially in its relations with the European Union. Meanwhile, Libya has to deal with the political and social challenge of African migrations. How migratory movements not only affect Libyan diplomacy but also reflect the domestic situation is what this paper is about.